Combined use of deformation and structural analysis for the structural damage assessment of heritage buildings: A case study in the Liguria region (Italy). (May 2023) - Lucio Sergio Sacco, Giulio; Ferrero, Chiara; Battini, Carlo; Calderini, Chiara
Highlights: Damage assessment of a historic masonry church exposed to slow-moving landslides. Combined used of deformation and structural analysis as main novelty. Displacement fields for structural analysis identified by deformation analysis. Causes of damage identified by FE modelling and nonlinear static analyses. Deformation analysis proven to be an effective tool to support structural analysis. Abstract: Cultural heritage buildings as they appear today are the result of continuous transformations occurred over the centuries. For this reason, their structural assessment should integrate structural analysis with a deep knowledge of the building history, actual geometry, damage, past alterations, and actions undergone over time. This paper presents the structural damage assessment of San Carlo Borromeo church, a historic masonry building located in the Liguria region (Italy) in a slow-moving landslide-affected area. To assess the effect of the landslide and identify the causes of the damage and deformations observed in the building, structural analysis was combined with historical research, on-site inspections, laser scanner survey and deformation analysis. A finite element model of the entire church in its geometric undeformed configuration was prepared by removing all the deformations identified through the deformation analysis from the actual deformed geometry obtained from the laser scanner survey. Nonlinear static analyses were then performed by applying at the base of the model a set of displacement fields obtained from the deformation analysis and representing the displacements experienced by the building due to the landslide and further phenomena that were found to have occurred. The damage and deformations predicted numerically were compared with those detected in the church. The good agreement proved that the deformation analysis is an effective tool to support structural analysis and assess the actual deformations and displacements experienced by historic masonry constructions.